The Effect of Paternal-Fetal Attachment Training on Marital Satisfaction during Pregnancy - Ashraf Nosrati; Kobra Mirzakhani; Nahid Golmakani; Seyyed Mohsen Asghari Nekah; Habibollah Esmaeili (Mashhad University of Medical Sciences, 2018)
Background & aim: Marital satisfaction during pregnancy is one of the factors affecting marital affectional bond. This study was performed to evaluate the effect of paternal-fetal attachment training on marital satisfaction during pregnancy. Methods: This clinical trial was conducted on 60 couples referring to two health centers of Mashhad, Iran, in 2015. The couples were randomly divided into intervention and control groups (n=30 couples in each group). The fathers in the intervention group participated in three 120-minute sessions of paternal-fetal attachment training and the mothers in both groups (intervention and control) received the routine prenatal care. Both groups were evaluated using Marital Satisfaction questionnaire of Nathan H Azarin before and three weeks after the intervention. To analyze the data, descriptive statistics, t-test, Chi-square test, Wilcoxon, Mann-Whitney U test, and analysis of covariance were performed using SPSS, version 22. Results: The mean score of marital satisfaction in men was significantly higher in the intervention group than the control group (P=0.003). The mean score of women's marital satisfaction in the intervention group increased after training from 62.63±2.58 to 66.50±2.43. However, there was no significant difference between two groups in terms of women's mean score of marital satisfaction (P=0.083). Conclusion: Paternal-fetal attachment training promoted marital satisfaction in men during pregnancy, so it is suggested to hold training programs for couples during pregnancy to enhance their marital satisfaction.